2018
DOI: 10.1016/j.anndiagpath.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and clinical performance of progesterone receptor antibodies in breast cancer

Abstract: Clones evaluated in this study had a high level of concordance with IHC despite PR (1E2) demonstrating higher analytical binding properties than other clones. In a minority of cases (1.3% for 1E2 and 2.5% for 636) IHC results could convert estrogen receptor (ER)-/PR- to ER-/PR+ tumors, making these patients potentially eligible for endocrine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Standard IHC assay of the ER discordant cases with the SP1 clone confirmed one case to be positive as assessed by MTP, while the other one remained negative (data not shown). In previous studies, the anti-human PR rabbit monoclonal 1E2 antibody showed higher analytical affinity for PR with respect to the 636 clone [13], [14]. Standard staining of PR discordant cases with the 1E2 clone confirmed two of the three cases to be positive as assessed by microfluidic assay, while one remained negative as by standard staining (data not shown).…”
Section: Discussionmentioning
confidence: 57%
“…Standard IHC assay of the ER discordant cases with the SP1 clone confirmed one case to be positive as assessed by MTP, while the other one remained negative (data not shown). In previous studies, the anti-human PR rabbit monoclonal 1E2 antibody showed higher analytical affinity for PR with respect to the 636 clone [13], [14]. Standard staining of PR discordant cases with the 1E2 clone confirmed two of the three cases to be positive as assessed by microfluidic assay, while one remained negative as by standard staining (data not shown).…”
Section: Discussionmentioning
confidence: 57%
“…Immunohistochemistry was performed using a VENTANA automated slide stainer (Roche Tissue Diagnostic, Almere, The Netherlands) according to the protocol from the manufacturer. All antibodies (Roche Tissue Diagnostic) 29 were used for clinical diagnosis and listed in Table 2 . For scoring purposes, all slides were subsequently scanned by using 3DHistech PANNORAMIC 250 Flash III DX (3DHistech, Budapest, Hungary) with 40× optical magnification at the Light and Electron Microscopy Facility of the LUMC.…”
Section: Methodsmentioning
confidence: 99%
“…SPR epitope binding analysis was done as previously described [ 25 , 26 ]. Briefly, SPR kinetic analyses of peptide binding of both clones was performed on a BIAcore T200 using Series S CM5 sensor chips.…”
Section: Methodsmentioning
confidence: 99%